PREVALENCE OF EXTENDED SPECTRUM BETA LACTAMASES AMONG GRAM NEGATIVE CLINICAL ISOLATES FROM A TERTIARY CARE HOSPITAL - A.VENKATA RAGHAVENDRA RAO,; K.S.SEETHA,; REENA RAJAN, (International Journal of Pharma and Bio Sciences, 2015)
Beta-lactamases production is the most common mechanism of bacterial resistance in gram negative bacteria. These enzymes are capable of mutation in response to the selective pressure of antibiotic use. This study was undertaken to detect the prevalence of Extended Spectrum β-lactamases (ESBLs) from Gram negative clinical isolates. A total of 500 gram negative isolates were subjected to Kirby Bauer disk diffusion method. Isolates showing resistance or reduced susceptibility to third generation cephalosporins were subjected to ESBL screening tests by Double Disc Synergy test and Phenotypic confirmatory disc diffusion test .The prevalence of ESBL producing Gram negative bacilli in this study was found to be 62%.A total of 310 isolates showed reduced susceptibility to third generation cephalosporins. Out of 310, 232(74.83%) isolates were positive for ESBL screening. All the 310 isolates were tested positive by confirmatory method. Early detection of these β-lactamases producing isolates in a routine laboratory could help to avoid treatment failure.